Feline blood genotyping versus phenotyping, and detection of non‐AB blood type incompatibilities in UK cats. (8th February 2014) - Tasker, S.; Barker, E. N.; Day, M. J.; Helps, C. R.
<x xml:space="preserve">Abstract</x> OBJECTIVES The aim of this study was to determine the agreement between AB blood phenotyping and genotyping and determine whether non‐AB blood type incompatibilities exist in UK cats. METHODS Blood samples underwent phenotyping (A, B or AB) using microplate agglutination, and genotyping (AA, Ab or bb) using pyrosequencing of a fragment of the cytidine monophospho‐N‐acetylneuraminic acid hydroxylase gene. Non‐AB blood type incompatibilities were investigated by cross‐matching against reference blood of the same phenotype. RESULTS Of 112 cats tested, 86 (77%) were blood phenotype A, 19 (17%) type B and 7 (6%) type AB. Genotype and initial phenotype agreed in 96% (107 of 112) of cats, but 5 were discordant; these were all B phenotype with either AA (n=2) or Ab (n=3) genotype. Two of the five cats had repeat blood samples tested: one was reclassified as phenotype A; the other remained phenotype B. Two cats had incompatibilities on minor cross‐match, but these were attributed to phenotyping errors. CLINICAL SIGNIFICANCE Unknown mutation(s) associated with phenotype B, resulting in false AA or Ab genotyping, were evident in a small number of cases in this study. No conclusive evidence for non‐AB blood type incompatibilities was found.